2014
DOI: 10.1155/2014/105492
|View full text |Cite
|
Sign up to set email alerts
|

Perforation Peritonitis and the Developing World

Abstract: Background. Perforation peritonitis is the one of the commonest emergency encountered by surgeons. The aim of this paper is to provide an overview of the spectrum of perforation peritonitis managed in a single unit of a tertiary care hospital in Delhi. Methods. A retrospective study was carried out between May 2010 and June 2013 in a single unit of the department of Surgery, Lok Nayak Hospital, Delhi. It included 400 patients of perforation peritonitis (diffuse or localized) who were studied retrospectively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
59
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 13 publications
15
59
4
Order By: Relevance
“…Peptic ulcer perforation is the most common cause for perforation peritonitis. 15,16 Most of the patients in our study i.e. 38 patients (84.5%) were male which is similar to other studies.…”
Section: Discussionsupporting
confidence: 90%
“…Peptic ulcer perforation is the most common cause for perforation peritonitis. 15,16 Most of the patients in our study i.e. 38 patients (84.5%) were male which is similar to other studies.…”
Section: Discussionsupporting
confidence: 90%
“…We found that surgery within the first six hour after diagnosis of perforation peritonitis had good outcomes in relations of earlier resumption of normal diet , shortening the length of stay in hospital and length of stay in ICU. Our overall mortality rate was 10%, which is lower [4][5][6][7] than reported by other studies. In comparision to early intervention patients, late intervention patients develop more postoperative complications (34.3 % vs. 17.8%, P=0.022).…”
Section: Discussioncontrasting
confidence: 76%
“…These observations were similar to studies of Bali RS showing mean age 37.8 years and male to female ratio of 2.1:1. 15 Similarly, Malik P also showed mean age 32 years and male to female ratio 2.8:1. 16 As many as 40 (80%) cases included in the present study, belonged to the low socioeconomic status (Table 1).…”
Section: Discussionmentioning
confidence: 89%